A case of Lewy body disease and anaplastic astrocytoma presenting with atypical parkinsonism. Issue 6 (12th July 2022) - Leahy, Christopher B; Robinson, Andrew C; Jabbari, Edwin; Morris, Huw R; Lally, Imogen; Djoukhadar, Ibrahim; Roncaroli, Federico; Kobylecki, Christopher
Abstract : We report on a patient with atypical parkinsonism due to coexistent Lewy body disease (LBD) and diffuse anaplastic astrocytoma. The patient presented with a mixed cerebellar and parkinsonian syndrome, incomplete levodopa response, and autonomic failure. The clinical diagnosis was multiple system atrophy (MSA). Supportive features of MSA according to the consensus diagnostic criteria included postural instability and early falls, early dysphagia, pyramidal signs, and orofacial dystonia. Multiple exclusion criteria for a diagnosis of idiopathic Parkinson's disease (iPD) were present. Neuropathological examination of the left hemisphere and the whole midbrain and brainstem revealed LBD, neocortical‐type consistent with iPD, hippocampal sclerosis, and widespread neoplastic infiltration by an anaplastic astrocytoma without evidence of a space occupying lesion. There were no pathological features of MSA. The classification of atypical parkinsonism was difficult in this patient. The clinical features and disease course were confounded by the coexistent tumor, leading to atypical presentation and a diagnosis of MSA. We suggest that the initial features were due to Lewy body pathology, while progression and ataxia, pyramidal signs, and falls were accelerated by the occurrence of the astrocytoma. Our case reflects the challenges of an accurate diagnosis of atypical parkinsonism, the potential for confounding co‐pathology and the need for autopsy examination to reach a definitive diagnosis.